PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH TERHADAP KINERJA GURU DI MADRASAH ALIYAH GHOYATUL JIHAD KABUPATEN KARAWANG - Addin, Fahma Nurfadilah; Bintang Kejora, Muhammad Taufik; Kosim, Abdul (Idaarah: Jurnal Manajemen Pendidikan, 2020)
This study aims to determine the effect of the principal's transformational leadership on the performance of teachers at Mdrasah Aliyah Ghoyatul Jihad, Karawang Regency. This study used a quantitative approach, correlative survey method with 23 respondents. Using saturated sampling and data collection techniques using an instrument in the form of a questionnaire. Data analysis used descriptive analysis using SPSS version 16.0 Windows software. The results showed that there was a positive and significant effect of transformational leadership on teacher performance with a Pearson correlation level of 0.848. The correlation was very strong. so that it can be interpreted that if there is a positive change in the transformational leadership score of one unit it will make a positive change in teacher performance. Based on the results of this study, it can be concluded that transformational leadership has a positive effect on teacher performance.